Original paperHealth-related quality of life in dermatological and allergo-dermatological patients - Świnoga, Magdalena; Kłos, Małgorzata; Miniszewska, Joanna; Zalewska-Janowska, Anna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2012)
Introduction: Health-related quality of life (HRQoL) denotes the effect of disease on patient’s daily functioning and well-being. Although mostly not life-threatening, dermatological diseases exert a significant impact on patient’s quality of life. Aim : The aim of the present study was to compare HRQoL between allergo-dermatological and dermatological patients in relation to different socio-demographic factors. Material and methods : One hundred patients of the Centre of Diagnosis and Treatment of Asthma and Allergy in Lodz were included in the study. The following methods were used: DLQI, Skindex-29, Pruritus Evaluation Questionnaire and Visual Analogue Scale. Results : Allergo-dermatological patients complained more often of such symptoms as burning, bleeding, pruritus and pain (burden of symptoms, Skindex-29) as compared to dermatological ones. The longer the disease duration, the lower HRQoL in allergo-dermatological patients was. In dermatological patients, more impaired HRQoL, measured by DLQI, was observed in males. Pruritus significantly impaired HRQoL in both studied groups. Conclusions : Pruritus intensity seems to be a very important factor decreasing patients’ HRQoL, thus psychomedical instruments should be focused on this symptom. Worse HRQoL in allergo-dermatological patients suffering longer from the disease should prompt to offer appropriate psychological help to this group of patients.